2024
DOI: 10.7150/thno.92350
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve-derived indole-3-lactic acid ameliorates colitis-associated tumorigenesis by directing the differentiation of immature colonic macrophages

Yuke Li,
Qingxiang Li,
Ruoshui Yuan
et al.

Abstract: Aim: To elucidate dynamics and functions in colonic macrophage subsets, and their regulation by Bifidobacterium breve (B. breve) and its associated metabolites in the initiation of colitis-associated colorectal cancer (CAC). Methods: Azoxymethane (AOM) and dextran sodium sulfate (DSS) were used to create a CAC model. The tumor-suppressive effect of B. breve and variations of macrophage subsets were evaluated. Intestinal macrophages were ablated to determine their role in the protective effects of B. breve. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Wang et al , reported that Lactobacillus-derived indole lactic acid could promote the expression of key bacterial enzymes implicated in tryptophan metabolism, leading to the synthesis of other indole derivatives including indole-3-propionic acid and indole-3-acetic acid, possessing the ability to reduce colonic inflammation. Anticolitis effect of indole lactic acid was also shown in previous studies conducted by Li et al and Wang et al Moreover, anti-inflammation effect of indole-3-carboxaldehyde has been recently recognized. Indole-3-carboxaldehyde has been shown to alleviate inflammation in the colon, liver, and kidney. , Although mechanisms underlying the benefits of indole derivatives remain exclusive, they may act as key PXR-modulating activators, subsequently attenuating inflammation by inhibiting NF-κB signaling. …”
Section: Discussionsupporting
confidence: 64%
“…Wang et al , reported that Lactobacillus-derived indole lactic acid could promote the expression of key bacterial enzymes implicated in tryptophan metabolism, leading to the synthesis of other indole derivatives including indole-3-propionic acid and indole-3-acetic acid, possessing the ability to reduce colonic inflammation. Anticolitis effect of indole lactic acid was also shown in previous studies conducted by Li et al and Wang et al Moreover, anti-inflammation effect of indole-3-carboxaldehyde has been recently recognized. Indole-3-carboxaldehyde has been shown to alleviate inflammation in the colon, liver, and kidney. , Although mechanisms underlying the benefits of indole derivatives remain exclusive, they may act as key PXR-modulating activators, subsequently attenuating inflammation by inhibiting NF-κB signaling. …”
Section: Discussionsupporting
confidence: 64%
“…ILA has the potential to regulate intestinal homeostasis by reducing the accumulation of inflammatory macrophages. 9 By increasing H3K27ac binding at the enhancer regions of IL12a, ILA facilitated the augmentation of IL12a production in dendritic cells, thereby promoting the stimulation of CD8 T cell immunity against tumor growth. Additionally, ILA exhibited the ability to enhance the activity of CD8 T cells present within the tumor microenvironment by modulating chromatin accessibility.…”
Section: Introductionmentioning
confidence: 99%